2014
DOI: 10.3906/sag-1301-61
|View full text |Cite
|
Sign up to set email alerts
|

Distal radius measurements and efficacy of fixed-angle locking volar plates

Abstract: Dairy and meat production are very complex in dry regions due to shortages and the low quality of fodder, especially in dry months. Livestock scientists are enthusiastic to explore and investigate good quality fodder that can boost milk and meat production in an economical way. Moringa oleifera is known as one of the best fodder crops for dry regions with scanty amounts of water. Hence, the present study was designed to evaluate the potential of Moringa oleifera as a field crop by harvesting at different cutti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Bassi et al (2003) measured the VCA of 50 normal lateral wrist radiographs; they reported a mean VCA of 37.1°. Agir et al (2014) measured the VCA in 18 dried adult cadaver radii using the lateral radiographic images; they reported that the mean value was 37.7°. These values are approximately 10° larger than those of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Bassi et al (2003) measured the VCA of 50 normal lateral wrist radiographs; they reported a mean VCA of 37.1°. Agir et al (2014) measured the VCA in 18 dried adult cadaver radii using the lateral radiographic images; they reported that the mean value was 37.7°. These values are approximately 10° larger than those of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our study validates prior studies that the VCA of our population does not anatomically match the VCA of current volar plate designs. 9,12,14 With a mean VCA of 32.2° in our cohort, the angles of current plates (18°-30°) would appropriately anatomically fit less than 16% of our population. As precontoured plates are often used as a template for reduction, current volar plate designs may not adequately reconstruct the distal radius and undercorrect the volar tilt.…”
Section: Discussionmentioning
confidence: 87%
“…11 Studies that examined cadaveric distal radii have shown that the precontoured angle of modern volar plates does not anatomically match the VCA of human cadavers 9 and that the VCA varies between individuals. 12 The purpose of this study was to measure the VCA of uninjured adult distal radii and determine whether the VCA predictably varies with patient demographics such as age and sex. Prior studies have failed to show a predictable association with age.…”
Section: Introductionmentioning
confidence: 99%
“…5 Currently, several therapeutic options are available: plaster casts, external fixators, percutaneous pin fixation, and modern locking volar plates. 1,6 Locking volar plates were introduced in clinical practice in the 1990s, showing excellent biomechanical results, 1,7 with fewer complications related to soft tissues than dorsal plates 6,[8][9][10][11][12] and allowing early wrist movement. 3,13 The main indications for locking volar plate treatment are: unstable extra-articular fractures (especially in osteoporotic bones), most articular fractures, and vicious consolidations of the distal third of the radius.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several therapeutic options are available: plaster casts, external fixators, percutaneous pin fixation, and modern locking volar plates. ( 1 , 6 …”
Section: Introductionmentioning
confidence: 99%